Modelling Factors influencing Behavioral Intention to Use Technology at University Education - غدير باسم; أحمد علي; العلي قصي (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The Purpose of the study is to build a model predicts the behavioural intention to use technology at university education by using the technology acceptance model (TAM) as a theoretical framework, and developing it by adding three new variables (Ability, Possibility, and University Factors) the researcher think they affect the behavioural intention to use technology. Data was collected from (285) participants using a survey questionnaire including (175) paper questionnaire and (110) electronic questionnaire using google forms services. The structural equation modelling (SEM) is used to test the research hypothesis. The hypothesized model was tested based on structural equation modelling and by using (SmartPLS V.3.3.2), to study the relationships among variables and to check the model fit. The resulting model is found to have a good fit. The perceived ease of use has indirect effect on behavioural intention by affecting the attitude toward using and perceived usefulness, whereas perceived usefulness has only indirect effect on behavioural intention. These used variables account for approximately (37.1%) of the variance of behavioural intention to use technology at university education.